Design of anti-load perturbation flight trajectory stability controller for agricultural UAV - Wei, Xu; XianYu, Wu; Jiazhen, Liu; Yasheng, Yan (Frontiers in Plant Science, 2023)
The unmanned aerial vehicle(UAV) used in agricultural fields usually has a load, which affects stability of flight trajectory. This problem is a great technical challenge and critical issue which has fascinated many researchers in this area. This research paper presents a flight dynamics model for agricultural UAV under load condition. The robust T-S fuzzy control method is applied in the attitude angle control part, and the traditional PID controller is used in the position loop control part. Results of simulation depict that the flight trajectory of agricultural UAV can reach certain stability when the load is relatively small.